Nucleologenesis in the Caenorhabditis elegans embryo - Korčeková, Darina; Gombitová, Adriána; Raška, Ivan; Cmarko, Dušan; Lanctôt, Christian (PloS one, 2012)
In the Caenorhabditis elegans nematode, the oocyte nucleolus disappears prior to fertilization. We have now investigated the re-formation of the nucleolus in the early embryo of this model organism by immunostaining for fibrillarin and DAO-5, a putative NOLC1/Nopp140 homolog involved in ribosome assembly. We find that labeled nucleoli first appear in somatic cells at around the 8-cell stage, at a time when transcription of the embryonic genome begins. Quantitative analysis of radial positioning showed the nucleolus to be localized at the nuclear periphery in a majority of early embryonic nuclei. At the ultrastructural level, the embryonic nucleolus appears to be composed of a relatively homogenous core surrounded by a crescent-shaped granular structure. Prior to embryonic genome activation, fibrillarin and DAO-5 staining is seen in numerous small nucleoplasmic foci. This staining pattern persists in the germline up to the ∼100-cell stage, until the P4 germ cell divides to give rise to the Z2/Z3 primordial germ cells and embryonic transcription is activated in this lineage. In the ncl-1 mutant, which is characterized by increased transcription of rDNA, DAO-5-labeled nucleoli are already present at the 2-cell stage. Our results suggest a link between the activation of transcription and the initial formation of nucleoli in the C. elegans embryo.
Keywords: embryo nesavčí; Caenorhabditis elegans Proteins; Animals; Cell Nucleolus; Nuclear Proteins; Transcription, Genetic; Embryo, Nonmammalian; genetická transkripce; zvířata; vývojová regulace genové exprese; jaderné proteiny; buněčné jadérko; proteiny Caenorhabditis elegans; Genome, Helminth; Gene Expression Regulation, Developmental; genom u helmintů; Caenorhabditis elegans